(untitled) (Journal of Nepal Physical Society, 2016)
We have studied the effect of phase difference between different multiple beams on the photoelectron angular distribution in three photon ionization of atomic hydrogen by using Dalgarno-Lewis methods. It has been found that both total and photo-electron angular distribution vary with laser intensity, phase and polarization of different beams. Intensity dependance of corresponding assymetry parameters has also been studied. We have shown that this variation with laser intensity is caused by two effects: the effect of phase and polarization of different beams. Asymmerties of azimuthal angular distribution are emphasized. Journal of Nepal Physical Society Vol.3(1) 2015: 18-22